2020
DOI: 10.1002/mco2.27
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in cancer progression and therapeutic strategies

Abstract: Dysregulated lipid metabolism represents an important metabolic alteration in cancer. Fatty acids, cholesterol, and phospholipid are the three most prevalent lipids that act as energy producers, signaling molecules, and source material for the biogenesis of cell membranes. The enhanced synthesis, storage, and uptake of lipids contribute to cancer progression. The rewiring of lipid metabolism in cancer has been linked to the activation of oncogenic signaling pathways and cross talk with the tumor microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 334 publications
(570 reference statements)
2
113
0
Order By: Relevance
“…However, myc has been found bound to the promoters of FA synthesis genes, such as the FASN and SCD genes, suggesting that it can also stimulate FA synthesis independently of SREBP1 [33]. Myc can also enhance the mitochondrial synthesis of acetyl-CoA and the de novo synthesis of palmitate [34] and has been shown to play a role in the regulation of FAO [23].…”
Section: Metabolic Alterations In Cancermentioning
confidence: 99%
“…However, myc has been found bound to the promoters of FA synthesis genes, such as the FASN and SCD genes, suggesting that it can also stimulate FA synthesis independently of SREBP1 [33]. Myc can also enhance the mitochondrial synthesis of acetyl-CoA and the de novo synthesis of palmitate [34] and has been shown to play a role in the regulation of FAO [23].…”
Section: Metabolic Alterations In Cancermentioning
confidence: 99%
“…Obesity has been recognized as a risk factor for cancer, so investigating lipid metabolism in the tumor is necessary. 233 , 234 The results of researches in the past 10 years have shown that abnormal lipid metabolism in the TME is one of the key steps involved in tumor metastasis. 235 Therefore, correcting abnormal lipid metabolism may prevent the occurrence of tumor metastasis.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…These include drugs targeting ETC, TCA, glycolysis, and fatty acid oxidation and synthesis enzymes. Some of these enzymes are localized in the mitochondria, whereas others are found in the cytosol (Figure 1 and Table 3) [7,[428][429][430][431][432][433][434][435][436][437][438]. In addition, increasing mitochondrial ROS production is also an important mitochondria-related cancer therapy strategy [14,20].…”
Section: Drugs Affecting Cellular Metabolismmentioning
confidence: 99%